2015
DOI: 10.17533/udea.iee.v33n3a12
|View full text |Cite
|
Sign up to set email alerts
|

The transition of palliative care from the hospital to the home: a narrative review of experiences of patients and family caretakers

Abstract: Objective. This work sought to identify, analyze, and synthesize the qualitative studies published on the experiences of patients and family caretakers during the transition of palliative care from the hospital to the home. Methodology. A narrative review was conducted on the PubMed, Cochrane Central, ScienceDirect, Ovid Nursing, CINALH, Scielo, and Bireme databases, from 2000 to 2014. Results. After the analysis and comparison of the data, the results were grouped into six themes: (1) the dyad and its knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…A narrative review of patient and family caregivers’ transition experiences of palliative care from the hospital to home setting showed that they experienced a broad range of needs during the transition process, including communication and information needs, emotional support and social support for family caregivers, which are not always addressed by healthcare professionals. 4 The review indicated a need to further explore the experiences of patients and families, especially during the stage prior to the transfer from the hospital to the home.…”
Section: Introductionmentioning
confidence: 99%
“…A narrative review of patient and family caregivers’ transition experiences of palliative care from the hospital to home setting showed that they experienced a broad range of needs during the transition process, including communication and information needs, emotional support and social support for family caregivers, which are not always addressed by healthcare professionals. 4 The review indicated a need to further explore the experiences of patients and families, especially during the stage prior to the transfer from the hospital to the home.…”
Section: Introductionmentioning
confidence: 99%
“…Family carers provide the majority of care at home in the last year of life (Ward-Griffin and McKeever 2000) and are thus essential for supporting home death (Gomes and Higginson 2006). Carers' tasks include physical care of the patient, medication and symptom management, household and daily activities, and providing emotional support (Aoun et al 2013;Arias Rojas and Garcı ´a-Vivar 2015;Barker et al 2017;Harris et al 2018). Results showed that all health professionals felt Carer-Help was a useful tool to increase carers' preparedness for attending to physical and emotional care needs of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A life-limiting illness is defined as an illness where it is expected that death will be a direct consequence (Palliative Care Australia 2018b). Carers report the need for disease-specific information relating to diagnosis, prognosis and treatment (Aoun et al 2013;Arias Rojas and Garcı ´a-Vivar 2015), and information and support relating to patient care needs (e.g. assistance with symptom and medication management, dressing, showering, transport to and from appointments) (Aoun et al 2013), practical support with household tasks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a review study show that family caregivers, during the transition of the palliative care of their patients from hospital to home, experience poor interaction on the part of the healthcare team and lack of coordination in the continuation of care at home, which adds to their stress and anxiety. 55 In a study, the researchers use a Multiple Sclerosis at Home Access model to provide a group of patients with full support and prevent the common complications of MS in their case. The key features of their plan include monthly visits at the patients' homes and the continuation of the caregiving process by professional caregivers.…”
Section: Discussionmentioning
confidence: 99%